PENGEMBANGAN PEMBELAJARAN IPS MODEL WEBBED DI SMK NEGERI 1 KALIANDA TAHUN 2012 - Jaya Wijaya; Pargito Pargito; Darsono Darsono (Faculty of Teacher Training and Education, University of Lampung, 2013)
The research was stimulated learning Social Studies in SMK Negeri 1 Kalianda model of discourse learning with a low learning achievement. This study aims to develop a model of learning by Webbed are (1) describe the analysis of needs students, (2) resulted in the design and teaching of learning syntax Social Studies Webbed models, (3) test the effectiveness of Social Studies Learning Model Webbed. The Social Studies model of learning development approach Webbed Research and Development (R D) following the research procedure Dick and Carey developed by Borg and Gall. The results of this research with an analysis of learning needs the students within the social studies model of Webbed compose the picture in determining the theme of potential areas suitable realities of life. The Syllabus mapping by analyzing the Content Standards, Competency Standards, and Indicators Basic Competence in the implementation of learning. Social studies learning scenario design and syntax Webbed models are (1) Introduction to aperception about Webbed models. (2) the analyze mapping Competency Standards, Basic Competencies and indicators, which define and determine the relationship between the themes in the learning network social studies Model Webbed by making the grille, instrument pre-test and post-test to look for gains in learning results. (3) Develop a learning relationship with Webbed Model social studies Themes. (4) Determine the formulation of the theme. (5) To collect data to answer the formulation of the theme. (6) The test formulation in the theme. (7) To formulate conclusions Webbed theme of learning models. Based on the test results in class X Accounting effectiveness, effectiveness scores 1.015 1. The Effectiveness based on the difference in pretest, posttest, and gain learning Webbed social studies models in experimental classes expressed more effective than the old model of learning in social studies class control. Keywords: Development, Sosial Studies Learning, Webbed Model